Surgical management of colorectal liver metastases: a European perspective. (January 2014) - Dunne, Declan FJ; Jones, Robert P; Malik, Hassan Z; Fenwick, Stephen W; Poston, Graeme J
SUMMARY  The treatment of colorectal cancer metastatic to the liver is increasingly complex as a result of changes in the patient population, advances in preoperative staging, changing definitions of resectability, advances in surgical technique and the expanding chemotherapeutic armamentarium. Management of these patients within a multidisciplinary team is increasingly important and associated with better outcomes. In patients with irresectable hepatic metastases, high secondary resection rates can be achieved with multiagent chemotherapy when managed in conjunction with a liver specialist. Perioperative mortality rates are reducing but morbidity remains high, and enhanced recovery could help reduce morbidity. Despite the advancing age and comorbidity of the patient population, multimodal management is likely to lead to further improvements in perioperative and long-term outcomes.